Electronic Pop-Up Books: Integrating Jambi Culture Icons to Contextualize Numerical Concepts In Early Childhood Islamic Education - Yusria Yusria; Elis Muslimah Nuraida; Diah Dwi Santri; Riri Marini (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2026)
This research aims to develop an innovative Electronic Pop-Up Book for Early Childhood Islamic Education students, focusing on contextualizing abstract mathematical numbers through Jambi cultural icons. This research method Using a Research and Development (R&D) approach with a Development Studies design, the media underwent rigorous validation by material and media experts, followed by practicality and effectiveness trials involving 21 students. The results categorized the media as